Observation of Transition‐Metal–Boron Triple Bonds in IrB2O− and ReB2O−. (9th June 2020) - Chen, Teng‐Teng; Cheung, Ling Fung; Chen, Wei‐Jia; Cavanagh, Joseph; Wang, Lai‐Sheng
Abstract: Multiple bonds between boron and transition metals are known in many borylene (:BR) complexes via metal dπ →BR back‐donation, despite the electron deficiency of boron. An electron‐precise metal–boron triple bond was first observed in BiB2 O − [Bi≡B−B≡O] − in which both boron atoms can be viewed as sp‐hybridized and the [B−BO] − fragment is isoelectronic to a carbyne (CR). To search for the first electron‐precise transition‐metal‐boron triple‐bond species, we have produced IrB2 O − and ReB2 O − and investigated them by photoelectron spectroscopy and quantum‐chemical calculations. The results allow to elucidate the structures and bonding in the two clusters. We find IrB2 O − has a closed‐shell bent structure ( Cs, 1 A ′) with BO − coordinated to an Ir≡B unit, ( − OB)Ir≡B, whereas ReB2 O − is linear ( C ∞v, 3 Σ − ) with an electron‐precise Re≡B triple bond, [Re≡B−B≡O] − . The results suggest the intriguing possibility of synthesizing compounds with electron‐precise M≡B triple bonds analogous to classical carbyne systems. Abstract : To bend or not to bend : Photoelectron spectroscopy and ab‐initio calculations show that IrB2 O − has a bent ( − OB)Ir≡B structure and ReB2 O − has a linear structure, [Re≡B−B≡O] − . The latter is the first example of a transition‐metal borylyne complex.